The application of the principles of effective schooling inSMP PIRI Ngaglik Sleman Yogyakarta Special Province - Ing Chhaypor (JOURNAL OF EDUCATION, 2010)
The purpose of this study was to reveal the implementation of the three components of effective schooling: inputs, processes, and outputs of SMP PIRI Ngaglik, Sleman, Yogyakarta Special Province. The qualitative method and narrative approach were used in this research study to analyze the data collected from observation, interview, and documentation. The results are as follows. (1) Inputs: The vision and mission of SMP PIRI Ngaglik are academically formulated and implemented well even though there are some obstacles occurring during the implementation processes such as the lack of human resources in the fields of computer, mathematics, and English. (2) Processes: The school management and leadership of SMP PIRI Ngaglik are termed as generally good. (3) Outputs: The academic achievements of SMP PIRI Ngaglik are quite high (93, 48 %) for the national examination at grade IX, even though the average scores of English, and mathematics of some students are still lower than the standard score (4.76)